Determinants Du Developpement Financier Dans Les Pays De La Zone Franc Cfa: Le Role De La Qualite Des Institutions - Kos à Mougnol Alice; Pr Kamajou François (European Scientific Journal, ESJ, 2016)
This paper aims at analysing the role of the quality of institutions (institutional factors) on financial development within the fourteen countries of the CFA Franc zone. For that purpose, the Pool Mean Group (PMG) method is used in order to estimate a linear model in dynamic panel data over the period 1996-2011. Findings show that the quality of some institutions (corruption, political stability, quality of regulation…) conditions or affects the improvement level of financial system of the above-listed countries. To contribute to the emergence of better developed finance and of course more productive, the paper stands for an “institutional convergence” as one of the assets of financial development in the CFA Franc countries.